Pendampingan Inovasi Teknologi Dalam Sistem Pembayaran di PT. Gecok Halal Indonesia - Naya, Candra; Fatchan, Muhamad; Permana, Indra; Fitriani (VINICHO MEDIA PUBLISINDO, 2024)
Assistance with technological innovation in payment systems at PT. Gecok Halal Indonesia